The Delivery of the Recombinant Protein Cocktail Identified by Stem Cell-Derived Secretome Analysis Accelerates Kidney Repair After Renal Ischemia-Reperfusion Injury - Kim, Ji Hyun; Yang, Heejo; Kim, Michael W.; Cho, Kang Su; Kim, Doo Sang; Yim, Hyung Eun; Atala, Zachary; Ko, In Kap; Yoo, James J. (Frontiers in Bioengineering and Biotechnology, 2022)
Recent advances in cell therapy have shown the potential to treat kidney diseases. As the treatment effects of the cell therapies are mainly attributed to secretomes released from the transplanted cells, the delivery of secretomes or conditioned medium (CM) has emerged as a promising treatment option for kidney disease. We previously demonstrated that the controlled delivery of human placental stem cells (hPSC)-derived CM using platelet-rich plasma (PRP) ameliorated renal damages and restored kidney function in an acute kidney injury (AKI) model in rats. The proteomics study of the hPSC-CM revealed that hPSC secrets several proteins that contribute to kidney tissue repair. Based on our results, this study proposed that the proteins expressed in the hPSC-CM and effective for kidney repair could be used as a recombinant protein cocktail to treat kidney diseases as an alternative to CM. In this study, we analyzed the secretome profile of hPSC-CM and identified five proteins (follistatin, uPAR, ANGPLT4, HGF, VEGF) that promote kidney repair. We investigated the feasibility of delivering the recombinant protein cocktail to improve structural and functional recovery after AKI. The pro-proliferative and anti-apoptotic effects of the protein cocktail on renal cells are demonstrated in vitro and in vivo. The intrarenal delivery of these proteins with PRP ameliorates the renal tubular damage and improved renal function in the AKI-induced rats, yielding similar therapeutic effects compared to the CM delivery. These results indicate that our strategy may provide a therapeutic solution to many challenges associated with kidney repair resulting from the lack of suitable off-the-shelf regenerative medicine products.